PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 KOTABARU - Abi Sara (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
The purpose of this study was to determine (1) Results of learning mathematics eighth grade students of SMP Negeri 2 Kotabaru using an approach Realistic Mathematic Education (RME) in the subject of surface area and volume of the cube and the beam. (2) The results of students' mathematics learning in class VIII SMP State 2 Kotabaru without using approaches Realistic Mathematic Education (RME) in the subject of surface area and volume of the cube and the beam. and (3) Effect on the use of the approach Realistic Mathematic Education (RME) on the mathematics learning outcomes Junior High School eighth grade students in the subject of 2 Kotabaru surface area and volume of the cube and the beam. The method used in this research is descriptive quantitative method, the population of all siswakelas VIII SMP Negeri 2 Kotabaru which amounts to 191 people. Sampling using random samples with the selected sample of 33 people in the class VIII B as the experimental class and 34 class VIII A as the control class. The instrument used is a test in the form of multiple choice questions the validity and reliabilitas.Teknik calculations using test data collection, observation and documentation. Data was analyzed using descriptive statistics with calculation of average, standard deviation and percentage calculations. Namely ujinormalitas prerequisite test analysis using Chi Square test and homogeneity test using duavarians homogeneity test. To test the hypothesis used t tests to determine the effect of Realistic approach Mathematic Education (RME) to students' mathematics learning outcomes. The results showed that there are significant Realistic approach Mathematic Education (RME) to the learning outcomes of mathematics siswakelas VIII SMP Negeri 2 Kotabaru, it is known from the results of hypothesis testing, by generating t = 2.15 and 1.67 on a level table = signifikanÎ± = 0 05. So that t (2.15)> t table (1.67) H0 ditolakdan Ha accepted. Keywords: Realistic Approach Mathematic Education (RME) and learning outcomes